Producer Insurance and Risk Management Options for Smallholder Farmers - Smith, Vincent H. (Published by Oxford University Press on behalf of the World Bank, 2018)
Many smallholder families are exceptionally prone to potentially catastrophic decreases in their incomes and access to food. Over the past decade, therefore, policy makers and economists have increasingly focused on potential mechanisms for expanding risk management strategies available to those families. Commercially provided weather-based index insurance products, perhaps partially funded by subsidies, have been of particular interest because of their apparent potential to provide payments to smallholder families when they are most in need of help. However, the empirical evidence from a wide range of studies indicates that, absent relatively substantial subsidies, small holder farmers will not purchase commercially priced index products or even “all risk” products where payments are tied to the farm's crop losses. There are three important reasons why this is the case. First, smallholder farmers already have many ways of managing their risks, including informal community-based initiatives, on-farm production decisions and off-farm work. Second, index insurance schemes are subject to considerable basis risk; families often do not receive an index insurance indemnity when they experience a substantial crop loss on their farms. Third, the fixed costs of delivering crop insurance to smallholders make such coverage expensive. The potential market for weather index insurance therefore may be limited to insuring relatively large groups of farmers, either directly or indirectly though providing micro finance and other lending institution with coverage against widespread loan defaults associated with catastrophic events like major droughts. Alternatively, weather indexes could simply be used to more accurately target emergency aid.